Digital Enterprise and Information Systems c - Ariwa, Ezendu; El-Qawasmeh, Eyas.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This volume constitutes the refereed proceedings of the International Conference on Digital Enterprise and Information Systems, held in London during July 20 - 22, 2011. The 70 revised full papers presented were carefully reviewed and selected. They are organized in topical sections on cryptography and data protection, embedded systems and software, information technology management, e-business applications and software, critical computing and storage, distributed and parallel applications, digital management products, image processing, digital enterprises, XML-based languages, digital libraries, and data mining.
Keywords: Computer science; Computer communication systems; Algorithms; Database management; Information storage and retrieval; Artificial intelligence; Computer Science; Information Systems Applications (incl. Internet).; Computer Communication Networks; Artificial Intelligence (incl. Robotics).; Information Storage and Retrieval; Algorithm Analysis and Problem Complexity; Database Management; Electronic books